DNA‐Based Nanocarriers to Enhance the Optoacoustic Contrast of Tumors In Vivo. Issue 2 (16th November 2020) - Joseph, James; Baumann, Kevin N.; Postigo, Alejandro; Bollepalli, Laura; Bohndiek, Sarah E.; Hernández‐Ainsa, Silvia
Abstract: Optoacoustic tomography (OT) enables non‐invasive deep tissue imaging of optical contrast at high spatio‐temporal resolution. The applications of OT in cancer imaging often rely on the use of molecular imaging contrast agents based on near‐infrared (NIR) dyes to enhance contrast at the tumor site. While these agents afford excellent biocompatibility and minimal toxicity, they present limited optoacoustic signal generation capability and rapid renal clearance, which can impede their tumor imaging efficacy. In this work, a synthetic strategy to overcome these limitations utilizing biodegradable DNA‐based nanocarrier (DNA‐NC) platforms is introduced. DNA‐NCs enable the incorporation of NIR dyes (in this case, IRDye 800CW) at precise positions to enable fluorescence quenching and maximize optoacoustic signal generation. Furthermore, these DNA‐NCs show a prolonged blood circulation compared to the native fluorophores, facilitating tumor accumulation by the enhanced permeability and retention (EPR) effect. In vivo imaging of tumor xenografts in mice following intravenous administration of DNA‐NCs reveals enhanced OT signals at 24 h when compared to free fluorophores, indicating promise for this method to enhance the optoacoustic signal generation capability and tumor uptake of clinically relevant NIR dyes. Abstract : Nanocarriers built through DNA nanotechnology are demonstrated to enhance the photoacoustic contrast of a small near‐infrared dye at the tumor site in vivo. These versatile, scalable, and biocompatible nanoplatforms provide interesting possibilities for in vivo cancer imaging as well as theranostics.